If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + -3 = y Combine like terms: -1 + -3 = -4 -4 = y Solving -4 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -4 + -1y = y + -1y Combine like terms: y + -1y = 0 -4 + -1y = 0 Add '4' to each side of the equation. -4 + 4 + -1y = 0 + 4 Combine like terms: -4 + 4 = 0 0 + -1y = 0 + 4 -1y = 0 + 4 Combine like terms: 0 + 4 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4
| 2x-35=6x+2 | | 2x+2-4=2/3 | | 15x+45=30 | | (2x-3)(2x+3)=135 | | -27+4x=7x+48 | | -2x^2+3x+9= | | 6-2x=-7+6 | | 4-n=10 | | -8x^2+9x+5= | | 8x-14=22 | | 99x+100=1 | | x^2+4x+4=44 | | 4a-1/3-3(a-2)=2 | | x-2y+3z=4 | | 14c+2=4 | | 2a+5=-2 | | 2x^2=22.126*22.125 | | -8=z/4 | | 6.6+x=0.9 | | 5d-3-3d=13 | | y=-32 | | 4b^2-36b+81=0 | | 2+x=x-2 | | 7r-4-8r=5 | | ab-9a+9b-81= | | 8n+2-9n=-8 | | 10x+15=8x+35 | | 5a^2-22a+8= | | (3x+2)(x+5)= | | 6x+1-3x=10 | | a-2-2a=10 | | 4m+2-2m=10 |